Assessing the quality of digital coproduction: An interdisciplinary model - Ina Radtke; Noortje Hoevens; Taco Brandsen; Marlies Honingh (Administrative Sciences, 2023)
The digital transformation of society raises high hopes for the improvement of the design and implementation of coproduction processes, which may lead to higher levels of acceptance, satisfaction, and trust with respect to public services. Yet and despite a growing number of studies on the role of digital technology on coproduction, our knowledge on how to assess the quality of digital coproduction is still very limited. The difficulty of defining quality indicators relates to three issues: the complexity of defining quality in public services, the lack of a clear understanding of quality in a coproduction process and the tendency to evaluate coproduction using the same approach as with other digitalised services. In this article, we adopt an interdisciplinary perspective to develop a conceptual model that builds on and bridges theoretical approaches commonly used to assess the quality of digital services, while adding elements that are specific to coproduction.
Keywords: 350; co-creation; coproduction; digitalization; public services; quality